Stabilization of Low‐Valent Iron(I) in a High‐Valent Vanadium(V) Oxide Cluster. Issue 46 (9th October 2017) - Anjass, Montaha H.; Kastner, Katharina; Nägele, Florian; Ringenberg, Mark; Boas, John F.; Zhang, Jie; Bond, Alan M.; Jacob, Timo; Streb, Carsten
Abstract: Low‐valent iron centers are critical intermediates in chemical and bio‐chemical processes. Herein, we show the first example of a low‐valent Fe I center stabilized in a high‐valent polyoxometalate framework. Electrochemical studies show that the Fe III ‐functionalized molecular vanadium(V) oxide (DMA)[Fe III ClV V 12 O32 Cl] 3− (DMA=dimethylammonium) features two well‐defined, reversible, iron‐based electrochemical reductions which cleanly yield the Fe I species (DMA)[Fe I ClV V 12 O32 Cl] 5− . Experimental and theoretical studies including electron paramagnetic resonance spectroscopy and density functional theory computations verify the formation of the Fe I species. The study presents the first example for the seemingly paradoxical embedding of low‐valent metal species in high‐valent metal oxide anions and opens new avenues for reductive electron transfer catalysis by polyoxometalates. Abstract : Iron in : The electrochemical formation and stabilization of a low‐valent iron(I) center within a high‐valent, molecular vanadium(V) oxide cluster gives (NH2 Me2 )[Fe I ClV V 12 O32 Cl] 5− . Experimental and theoretical studies provide insight into the electronic structure, reactivity, and stability of the species. The study opens new pathways for isolating and stabilizing low‐valent transition‐metal centers in high‐valent polyoxometalate clusters.